Jenis dan Tingkat Parasitasi Parasitoid Larva Plutella xylostella L. pada Tanaman Sawi Hijau (Brassica juncea L.) - Syarifah Tuti Alawiyah; Yuni Ratna; Weni Wilia (Jurnal Media Pertanian, 2023)
The purpose of this study was to determine the type and level of parasitoidparasitization larvae of P. xylostella on mustard greens (B. juncea). This research was carried out from August to October 2022 in the Lingkar Selatan Village, Jambi City and Tangkit Village, Muaro Jambi Regency. Identification of types of parasitoids and calculation of parasite levels were carried out at the Laboratory of Plant Pests, Faculty of Agriculture, Jambi University. For each green mustard planting area in the two study locations, 3 random sample plots were determined. The technique for determining sample plants uses a systematic random method with a pattern of plant lanes. Sampling of P. xylostella larvae was carried out at the age of 4, 9 and 13 days after planting (DAP). The larvae of P. xylostella were reared in the laboratory to find out the parasitoids that appeared, then identified based on their morphological characteristics. The type of parasitoid larvae of P. xylostella found in both study locations was Cotesia plutellae. The level of parasitoid parasitization in the Lingkar Selatan Village was always higher at various ages of plants with an average of 39.92% compared to Tangkit Village, which was 12.4%.Keywords: mustard greens,P. xylostella, Cotesia plutellae,level of parasitoid parasitization